2022
DOI: 10.1101/2022.01.03.474851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insights into an evolutionary turning-point of photosystem I from prokaryotes to eukaryotes

Abstract: Photosystem I (PSI) contributes to light-conversion reactions; however, its oligomerization state is variable among photosynthetic organisms. Herein we present a 3.8-Å resolution cryo-electron microscopic structure of tetrameric PSI isolated from a glaucophyte alga Cyanophora paradoxa. The PSI tetramer is organized in a dimer of dimers form with a C2 symmetry. Different from cyanobacterial PSI tetramer, two of the four monomers are rotated around 90°, resulting in a totally different pattern of monomer-monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…As a short-term light acclimation mechanism in response to fluctuating illumination and anoxia, the algal PSI additionally associates with two LHCII trimers 5,6 . Structural studies have shown that the oligomeric state of a chloroplast PSI is a monomer, due to the presence of the subunit PsaH, whereas in cyanobacteria structures of dimers [7][8][9][10] and trimers 11 were also reported. Cyanobacterial PSI oligomerizes via direct contacts between subunits PsaI and PsaL, however such an association has been ruled out for a chloroplast PSI due to structural constraints of PsaH presence that imposes an apparent rigidity 12,13 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…As a short-term light acclimation mechanism in response to fluctuating illumination and anoxia, the algal PSI additionally associates with two LHCII trimers 5,6 . Structural studies have shown that the oligomeric state of a chloroplast PSI is a monomer, due to the presence of the subunit PsaH, whereas in cyanobacteria structures of dimers [7][8][9][10] and trimers 11 were also reported. Cyanobacterial PSI oligomerizes via direct contacts between subunits PsaI and PsaL, however such an association has been ruled out for a chloroplast PSI due to structural constraints of PsaH presence that imposes an apparent rigidity 12,13 .…”
Section: Mainmentioning
confidence: 99%
“…2a). In cyanobacteria, PSI dimerises via the stromal region of PsaL 710 and trimerises via the lumenal C-terminus of PsaL, assisted by PsaI 11 . In our structure of the chloroplast PSI-LHCI dimer, neither PsaL nor PsaI interacts with each other between the neighbouring units.…”
Section: Mainmentioning
confidence: 99%
“…CryoEM maps of all these 16 protein complexes (A) were released in the EMDB 20 within a single week (10-16 February 2022). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The total number of structures released in that week was 121. Here, only some of these structures, whose resolution reached better than 4 Å, and for which atomic models were deposited in the PDB, are shown.…”
Section: Entering An Era Of Plenty In Structural Biologymentioning
confidence: 99%